Model Kegiatan Sosialisasi Pencegahan Dan Penanganan Covid-19 Terhadap Masyarakat - M. Habib Husnial Pardi M. Habib Husnial Pardi; Abdul Manap; Busyairi Busyairi; Nur Hariadi Nur Hariadi; Putri Diana Putri Diana (Prodi Tadris Matematika-UIN Mataram, 2022)
This community service activity was carried out in order to increase public self-awareness during the Covid-19 pandemic in several villages including Prai Meke Village, Tamansari Village, Babusssalam Village, Sesela Village, and Montong Terep Village. The methods used in community service are socialization and question and answer. The data collection used is observation, interview, and documentation. The results of this community service are in the form of increasing public understanding of the importance of 6M and vaccination in the midst of a pandemic which is expected to be able to embrace the community in several villages in dealing with Covid-19 so that they are stronger in maintaining the readiness and protecting themselves from being exposed to an increasingly rampant pandemic.